Markers of intestinal permeability are rapidly improved by alcohol withdrawal in patients with alcohol-related liver disease - Jung, Finn; Burger, Katharina; Staltner, Raphaela; Brandt, Annette; Mueller, Sebastian; Bergheim, Ina (Nutrients, 2021)
Changes in intestinal microbiome and barrier function are critical in the development of alcohol-related liver disease (ALD). Here, we determined the effects of a one-week alcohol withdrawal on parameters of intestinal barrier function in heavy drinkers with ALD in comparison to healthy non-drinkers (controls). In serum samples of 17 controls (m = 10/f = 7) and 37 age-matched ALD patients (m = 26/f = 11) undergoing a one-week alcohol withdrawal, markers of liver health and intestinal barrier function were assessed. Liver damage, e.g., fibrosis and hepatic steatosis, were assessed using FibroScan. Before alcohol withdrawal, markers of liver damage, lipopolysaccharide binding protein (LBP) and overall TLR4/TLR2 ligands in serum were significantly higher in ALD patients than in controls, whereas intestinal fatty acid binding protein (I-FABP) and zonulin protein concentrations in serum were lower. All parameters, with the exception of LBP, were significantly improved after alcohol withdrawal; however, not to the level of controls. Our data suggest that one-week of abstinence improves markers of intestinal barrier function and liver health in ALD patients.